Optimizing the performance of gasoline-ethanol-methanol fueled engines with variations in the air-fuel ratio - Mokhtar; Danardono Agus Sumarsomo; Askar Adika Agama; Mohammad Adhitya (BKS-TM Indonesia, 2025)
The 125 cc, four-stroke, air-cooled, electronic fuel injection SI engine for motorcycles was used to compare the effects of mixing methanol and ethanol with gasoline on engine power, fuel efficiency, and engine emissions. The test took place on the engine test bench. the fuel blending variation is 80% gasoline with various methanol-ethanol percentages. The result shows that The maximum torque value of all fuel mixture variants is achieved in the M20 mixture at λ= 0.9 at 6000 RPM, namely 8.52 Nm. The power value shows the highest value in the M20 mixture with λ= 1.1, namely 6.45 kW and the lowest value of SFC is 266.3 g/KWh obtained by the E10M10 mixture at 6000 RPM engine speed at λ=1.3